National Cultural Diversity Based on Interactive Multimedia: Elementary School Teachers' and Students' Responses to the Implementation of the Curriculum Merdeka - Gunardi, Ari; Hidayat, Sholeh; Ruhiyat, Yayat (STKIP Singkawang, 2024)
Learning media plays an important role in improving students' learning abilities. One measure of student success is the application of interactive media implemented by teachers. The purpose of this study was to describe the responses of teachers and fourth grade elementary school students to the use of social studies learning media on the material